The Influence of LMS-Based Blended Learning Models on Learning Motivation and Learning Outcomes in Network Infrastructure Administration. - Devi Zetira Fauziah; Basori Basori; Dwi Maryono (Journal of Informatics and Vocational Education, 2021)
This study aims to find out how much increased learning motivation and student learning outcomes in using the blended learning model. The study involved class XI TKJ students at SMK Sakti Gemolong as participants, who were selected using cluster random sampling techniques. The treatment given to the experimental class is in the form of a blended learning model, while the control class is with conventional learning. The research method used is quantitative. Data were collected by questionnaire method and learning achievement test. Analysis of the questionnaire is used to get data on student motivation. Then to analyze the test of learning outcomes is get to obtain data on student learning outcomes. The study found 1) there is a significant influence of student learning motivation by .209 which means greater than the level of error (0.05). 2) there is a significant influence of learning outcomes of .698 which means it is greater than the level of error (0.05). 3) there is effectiveness in increasing students' learning motivation by using blended learning models with a total score gain of 0.2028. Compared to using conventional learning with a total score gain of 0.0735. 4) there is an effectiveness in increasing student learning outcomes by using a blended learning model with a total score gain of 0.4810. Compared to using conventional learning with a total score gain of 0.2176.